2014
DOI: 10.1128/jvi.02777-14
|View full text |Cite
|
Sign up to set email alerts
|

Blocking ESCRT-Mediated Envelopment Inhibits Microtubule-Dependent Trafficking of Alphaherpesviruses In Vitro

Abstract: Herpes simplex virus (HSV) and, as reported here, pseudorabies virus (PRV) utilize the ESCRT apparatus to drive cytoplasmic envelopment of their capsids. Here, we demonstrate that blocking ESCRT-mediated envelopment using the dominant-negative inhibitor Vps4A-EQ (Vps4A in which glutamate [E] at position 228 in the ATPase active site is replaced by a glutamine [Q]) reduced the ability of HSV and PRV particles to subsequently traffic along microtubules in vitro. HSV and PRV capsid-associated particles with bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 58 publications
5
53
0
Order By: Relevance
“…3). The former resemble in size and appearance the assembly intermediates that we have described earlier, a subset of which are motile along microtubules in vitro (16). The latter, which are more abundant in Vero (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…3). The former resemble in size and appearance the assembly intermediates that we have described earlier, a subset of which are motile along microtubules in vitro (16). The latter, which are more abundant in Vero (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…This fraction contains the organelles to which HSV capsids traffic from the nucleus during a single synchronized wave of egress and is the first compartment at which fully enveloped infectious virions accumulate in the cytoplasm (60). HSV capsids enveloping in this gradient fraction also acquire molecular motors and become capable of traffic along microtubules in vitro (16,42,63). Biochemical analyses and electron microscopy revealed that this region of the gradient contains fully enveloped HSV particles within organellar lumens, and nonenveloped capsids docked to the cytoplasmic faces of the organelles (60).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations